2016
DOI: 10.5815/ijieeb.2016.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Shape Image Retrieval Using DNN and ELM Classifiers for MRI Brain Tumor Images

Abstract: The problem of searching a digital image in a very huge database is called Content Based Image Retrieval (CBIR). Shape is a significant cue for describing objects. In this paper, we have developed a shape feature extraction of MRI brain tumor image retrieval. We used T1 weighted image of MRI brain tumor images. There are two modules: feature extraction process and classification. First, the shape features are extracted using techniques like Scale invariant feature transform (SIFT), Harris corner detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…They have shown that by using hybrid features some improvement in the retrieval accuracy can be obtained. A. Anbarasa Pandian and R. Balasubramanian [26] have applied the CBIR technique for the MRI brain tumor images dataset. They used a shape feature for this.…”
Section: Existing Work In Cbirmentioning
confidence: 99%
“…They have shown that by using hybrid features some improvement in the retrieval accuracy can be obtained. A. Anbarasa Pandian and R. Balasubramanian [26] have applied the CBIR technique for the MRI brain tumor images dataset. They used a shape feature for this.…”
Section: Existing Work In Cbirmentioning
confidence: 99%
“…𝐻 † = (𝐻 𝑇 𝐻) βˆ’1 𝐻 𝑇 (8) Secara lebih ringkas, algoritma ELM dengan SLFN dapat dimodelkan dengan langkah sebagai berikut [20], [12], [21], [22]. Input : Data training (π‘₯ 𝑖 , 𝑦 𝑖 ) dengan π‘₯ 𝑖 = [π‘₯ 𝑖1 , π‘₯ 𝑖2 , … , π‘₯ 𝑖𝑑 ] 𝑇 ∈ 𝑅 𝑑 dan 𝑦 𝑖 = [𝑦 𝑖1 , 𝑦 𝑖2 , … , 𝑦 π‘–π‘š ] 𝑇 ∈ 𝑅 π‘š .…”
Section: 𝐻𝛽 = π‘Œunclassified
“…In the study [19] the authors developed an extraction of shape features form MRI brain tumor image. The supervised learning algorithms like Deep Neural Network and Extreme Learning Machine are used to classify the brain tumor images.…”
Section: Related Workmentioning
confidence: 99%